Paleoecological and climatic implications of stable isotope results from late Pleistocene bone collagen, Ziegeleigrube Coenen, Germany. Issue 1 (July 2015) - Wißing, Christoph; Matzerath, Simon; Turner, Elaine; Bocherens, Hervé
Abstract : Climatic and ecological conditions during Marine Oxygen Isotope Stage (MIS) 3 are complex and the impact of cold spells on the ecosystems in Central Europe still needs to be investigated thoroughly. Ziegeleigrube Coenen (ZC) is a late Pleistocene MIS 3 locality in the Lower Rhine Embayment of Germany, radiocarbon-dated to > 34 14 C ka BP. The site yielded a broad spectrum of mammal species. We investigated the carbon (δ 13 C), nitrogen (δ 15 N) and sulfur (δ 34 S) isotope signatures of bone collagen, since these are valuable tools in characterizing ecological niches, environmental conditions and aspects of climate and mobility. By comparison with pre- and post-Last Glacial Maximum (LGM) sites in Central Europe we show that ZC belongs in a cold event of MIS 3 and was climatically more similar to post-LGM sites than to pre-LGM sites. However, the trophic structure resembled that of typical pre-LGM sites in Belgium. This cold event in MIS 3 changed the bottom of the foodweb, but do not seem to have had a direct impact on the occurrence of the mammalian species and their ecological distribution. Apparently the (mega-) faunal community could adapt also to harsher environmental conditions during MIS 3.